A classification system for zebrafish adipose tissues - Minchin, James E. N. (Dis Model Mech, 2017)
The zebrafish model system offers significant utility for in vivo imaging of adipose tissue (AT) dynamics and for screening to identify chemical and genetic modifiers of adiposity. In particular, AT can be quantified accurately in live zebrafish using fluorescent lipophilic dyes. Although this methodology offers considerable promise, the comprehensive identification and classification of zebrafish ATs has not been performed. Here, we use fluorescent lipophilic dyes and in vivo imaging systematically to identify, classify and quantify the zebrafish AT pool. We identify 34 regionally distinct zebrafish ATs, including five visceral ATs and 22 subcutaneous ATs. For each of these ATs, we describe detailed morphological characteristics to aid their identification in future studies. Furthermore, we quantify the areas for each AT and construct regression models to allow prediction of expected AT size and variation across a range of developmental stages. Finally, we demonstrate the utility of this resource for identifying effects of strain variation and high-fat diet on AT growth. Altogether, this resource provides foundational information on the identity, dynamics and expected quantities of zebrafish ATs for use as a reference for future studies.